COVID-19 pandemic-related weight gain in the pediatric population declined after restrictions ended, except among obese patients - Irschik, Stefan; Brandt, Jennifer B.; Eisenkölbl, Johannes (Frontiers in Public Health, 2023)
Introduction: Childhood obesity has been an important topic of increasing relevance not only during but enhanced by the COVID-19 pandemic. Associated restrictions to mitigate further outbreaks led to massive restrictions on daily physical activities and therefore, to severely increased body weight of children. This study highlights changes of BMI and the weight development in children during and especially after COVID-19 restrictions in Austria, focusing on various socioeconomic factors. Methods: Weight development throughout the pandemic and socioeconomic factors were evaluated by anonymous cross-sectional surveys filled out by parents in a pediatrician practice. Results: This study included 388 children. The rate of obesity increased by 88.5% from 6.4% to 12.1% throughout the pandemic with a maximum of 15.2% during the restrictions. Overall the age adapted BMI z-scores increased significantly by 0.22 during the restrictions and stayed increased by 0.19 compared to pre-pandemic levels. Except for the obese children of the study population, all children had significant weight loss after the restrictions were lifted. Obese children kept gaining weight, without any sign of beginning normalization. Socioeconomic factors as regular activity in a form of organized sport or availability of an outdoor area showed relevant differences before the pandemic but had no protective effect on intra-pandemic weight gain. Only a higher parental education led to better performance during the early phase of the pandemic. Discussion: Austrian COVID-19 restrictions have had concerning effects on pediatric BMI, hardly affected by the socioeconomic background. After restrictions were loosened, weight-loss was measurable, but BMI percentiles persisted significantly increased. No weight-loss was observed for pre-pandemic obese children. There is need for broad projects tackling childhood obesity as they are the most vulnerable group with the strongest and most severe long-term effects.